1984
DOI: 10.1068/p130601
|View full text |Cite
|
Sign up to set email alerts
|

Acuity of Sound Localisation: A Topography of Auditory Space. II. Pinna Cues Absent

Abstract: The acuity of azimuth and elevation discrimination was measured under conditions in which the cues to localisation provided by the pinnae were removed. Four subjects localised a sound source (white noise through a speaker) which varied in position over a range of elevations (-40 degrees to +40 degrees) and azimuths (0 degree to 180 degrees), at 10 degrees intervals, on the left side of the head. Pinna cues were removed by the insertion of individually cast moulds in both pinnae. Each mould had an access hole t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
61
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 12 publications
13
61
1
Order By: Relevance
“…For example, altering the spectral cues with pinna molds abolishes elevation localization but leaves azimuth performance intact (Oldfield and Parker, 1984;. Moreover, human listeners can adapt to modified spectral cues and relearn to localize elevation without changing their azimuth performance .…”
Section: Introductionmentioning
confidence: 99%
“…For example, altering the spectral cues with pinna molds abolishes elevation localization but leaves azimuth performance intact (Oldfield and Parker, 1984;. Moreover, human listeners can adapt to modified spectral cues and relearn to localize elevation without changing their azimuth performance .…”
Section: Introductionmentioning
confidence: 99%
“…Auditory stimuli are initially encoded in a head-centered reference frame; the spatial coordinates of auditory targets are extracted from interaural differences in arrival time and level. The sound emitted by a source is diffracted by its interaction with the head and external ears, and the resulting changes in the temporal characteristics and intensity provide cues about the location of the sound relative to the head (Hofman & Van Opstal, 1998;Middlebrooks, 1992;Oldfield & Parker, 1984). When action is required, the representation of sensory stimuli often must be transformed into another reference frame.…”
mentioning
confidence: 99%
“…Several studies have shown that listeners with one ear plugged retain a respectable ability to determine the elevation and front-back hemifield of a free-field sound source (e.g., Fisher and Freedman 1968;Oldfield and Parker 1986;Butler et al 1990;Slattery and Middlebrooks 1994). This finding suggests that monaural spectral cues provide sufficient information for some aspects of a sound-source's location to be determined.…”
Section: Introductionmentioning
confidence: 69%